The Extra Virgin Olive Oil Polyphenol Oleocanthal Exerts Antifibrotic Effects in the Liver - Gabbia, Daniela; Carpi, Sara; Sarcognato, Samantha; Cannella, Luana; Colognesi, Martina; Scaffidi, Michela; Polini, Beatrice; Digiacomo, Maria; Esposito Salsano, Jasmine; Manera, Clementina; Macchia, Marco; Nieri, Paola; et al. (Frontiers in Nutrition, 2021)
Liver fibrosis, which is the outcome of wound-healing response to chronic liver damage, represents an unmet clinical need. This study evaluated the anti-fibrotic and anti-inflammatory effects of the polyphenol oleocanthal (OC) extracted from extra virgin olive oil (EVOO) by an in vitro/in vivo approach. The hepatic cell lines LX2 and HepG2 were used as in vitro models. In vivo, OC was administered daily by oral gavage to Balb/C mice with CCl4-induced liver fibrosis. The expression of pro-fibrogenic (SMA, COL1A1) and inflammatory (IL6, IL17, IL23, CCL2, CXCL12) genes, and selected miRNAs (miR-181-5p, miR-221-3p, miR-29b-3p and miR-101b-3p) were assessed by qRT-PCR. We demonstrated that OC significantly decreased the levels of SMA, COL1A1 and a panel of metalloproteinases (MMP2, MMP3, MMP7) involved in fibrogenesis, as well as the oxidative enzymes NOX1/4 in TGF1-activated LX2 cells. In vivo, OC, beside causing a significant reduction of fibrosis at histological assessment, counteracted the CCl4-induced upregulation of pro-fibrotic and inflammatory genes. Moreover, OC restored the physiological levels of the anti-fibrotic miRNAs miR-29b-3p and miR-101b-3p, reduced in fibrotic mice, while downregulated the pro-fibrotic miRNAs miR-221-3p and miR-181-5p. In conclusion, OC exerts a promising effect via a combined reduction of oxidative stress and inflammation involving putative miRNAs, which in turn reduces hepatic stellate cells activation and liver fibrosis.